Tetrathiafulvalene esters with high redox potentials and improved solubilities for non-aqueous redox flow battery applications - Weikang Hu; Jiaqi Xu; Nanjie Chen; Zongcai Deng; Yuekun Lai; Dongyang Chen (Green Energy & Environment, 2024)
The exploitation of high performance redox-active substances is critically important for the development of non-aqueous redox flow batteries. Herein, three tetrathiofulvalene (TTF) derivatives with different substitution groups, namely TTF diethyl ester (TTFDE), TTF tetramethyl ester (TTFTM), and TTF tetraethyl ester (TTFTE), are prepared and their energy storage properties are evaluated. It has been found that the redox potential and solubility of these TTF derivatives in conventional carbonate electrolytes increases with the number of ester groups. The battery with a catholyte of 0.2 mol L−1 of TTFTE delivers a specific capacity of more than 10 Ah L−1 at the current density of 0.5 C with two discharge voltage platforms locating at as high as 3.85 and 3.60 V vs. Li/Li+. Its capacity retention can be improved from 2.34 Ah L−1 to 3.60 Ah L−1 after 100 cycles by the use of an anion exchange membrane to block the crossover of TTF species. The excellent cycling stability of the TIF esters is supported by their well-delocalized electrons, as revealed by the density function theory calculations. Therefore, the introduction of more and larger electron-withdrawing groups is a promising strategy to simultaneously increase the redox-potential and solubility of redox-active materials for non-aqueous redox flow batteries.